The integration of ln x is equal to xln x -x+C where C is an integral constant. Ln x denotes the natural logarithm of x, that is, ln x=log_{e}x. The integration of lnx is denoted by the symbol ∫ln(x) dx. In this post, we will learn how to integrate ln x.

The formula of the integration of lnx is given below:

∫ln(x) dx = xln(x) -x+C where ln(x) = log_{e}x.

## How to integrate lnx?

To find the integral of lnx, we will use the integration by parts formula. The formula is given below.

∫uv dx = u∫v dx -∫[$\frac{du}{dx}$∫v dx] dx.

Here, we put u=lnx and v=1.

So ∫ln(x) dx = $\int \ln x \cdot 1 \ dx$

= $\ln x \int 1\ dx -\int \big[\dfrac{d}{dx}(\ln x) \int 1\ dx \big]dx$

= $\ln x \times x -\int \big[\dfrac{1}{x} \times x \big]dx$ + C

= $x\ln x -\int dx + C$

= $x\ln x -x+C$

So the integration of lnx is equal to xlnx-x+C and this is derived using the integration by parts formula

**Question:** Find integral of lnx from 1 to 2.

*Answer:*

From above, we have $\int \ln x \ dx = x\ln x -x$. So we obtain that

$\int_1^2 \ln x \ dx = \big[x\ln x -x \big]_1^2$

= (2ln2 – 2) -(ln1 – 1)

= 2ln2 -2 +1 as ln1=0

= 2ln2 – 1.

Thus, the integration of lnx from 1 to 2 is equal to 2ln2 – 1.

**ALSO READ:**

## FAQs on Integration of lnx

**Q1: What is the integration of lnx?**

**Answer:** The integration of lnx is equal to xlnx-x+C where C is an integration constant.